Leg ulcer treatment by superficial vein surgery and saline-gauze dressing - Dagilaitis, Rolandas; Triponis, Vytautas; Gudgalytė, Ingrida; Triponienė, Dalia (Lietuvos chirurgija, 2007)
Rolandas Dagilaitis,  Vytautas Triponis, Ingrida Gudgalytė,  Dalia TriponienėVilnius University Centre of Vascular Surgery,Antakalnio str. 57, LT-10207 Vilnius, LithuaniaE-mail: vytautas.triponis@mf.vu.ltObjectiveTo determine the effectiveness of phlebectomy and topic saline in patients with leg ulcer caused by isolated superficial vein reflux.Materials and methodsOne hundred and thirty consecutive patients with 143 ulcers were operated for superficial varicose veins and venous ulcer. Patients with deep reflux, peripheral arterial disease (ankle/brachial index 6 cm respectively. The healing process was complete in 135 (94.4%) ulcers at 1 year. One healed ulcer (0.7%) recurred between 6 and 12 months, 7 ulcers >6 cm showed reepithelialization being in process.ConclusionPhlebectomy in cases of isolated superficial vein reflux is able to heal venous ulcers in majority of patients. The healing rate was correlative with ulcer size and duration. Surgery plus saline-gauze local treatment significantly reduced the costs of venous ulcer treatment.Key words: leg ulcer, superficial vein surgery, topical treatment